Are soil testate amoebae and diatoms useful for forensics?. (August 2018) - Wanner, Manfred; Betker, Elisa; Shimano, Satoshi; Krawczynski, René
Highlights: Testate amoebae and diatoms are promising for PMI estimation and site location. Testate amoebae abundances are considerably affected by cadaveric fluids. Carcass influence on soil protists may be superimposed by natural effects Abstract: Two of the main goals of forensic science are (1) to estimate the time since death, or post mortem interval (PMI) and (2) to find the site where a dead body was buried. Soil testate amoebae and diatoms may be useful indicators for these goals. However, the structure and patchiness of the habitat appears to be a main driver for the amoeba and diatom soil communities (e.g., individual density). In case the soil substrate is very dry and nutrient-poor (as in our study), the influence of a dead body on the soil microfaunal community may be superimposed by natural environmental heterogeneity, especially soil moisture content. Further studies are necessary to clarify if protist abundance data are helpful for forensic investigations.